Modulations of NeuroD Activity Contribute to the Differential Effects of Morphine and Fentanyl on Dendritic Spine Stability - Zheng, Hui (Society for Neuroscience, 2010)
The cellular level of neurogenic differentiation 1 (NeuroD) is modulated differentially by μ-opioid receptor agonists; fentanyl increases NeuroD level by reducing the amount of microRNA-190 (miR-190), an inhibitor of NeuroD expression, whereas morphine does not alter NeuroD level. In the current study, NeuroD activity was demonstrated to be also under agonist-dependent regulation. After 3 d of treatment, morphine and fentanyl decreased the activity of the Ca(2+)/calmodulin-dependent protein kinase II α (CaMKIIα), which phosphorylates and activates NeuroD. Because NeuroD activity is determined by both the CaMKIIα activity and the cellular NeuroD level, the overall NeuroD activity was reduced by morphine, but maintained during fentanyl treatment. The differential effects of agonists on NeuroD activity were further confirmed by measuring the mRNA levels of four NeuroD downstream targets: doublecortin, Notch1, neurogenic differentiation 4, and Roundabout 1. Decreased dendritic spine stability and μ-opioid receptor signaling capability were also observed when NeuroD activity was attenuated by miR-190 overexpression or treatment with KN93, a CaMKIIα inhibitor. The decrease could be rescued by NeuroD overexpression, which restored NeuroD activity to the basal level. Furthermore, elevating NeuroD activity attenuated the morphine-induced decrease in dendritic spine stability. Therefore, by regulating NeuroD activity, μ-opioid receptor agonists modulate the stability of dendritic spines.